2020
DOI: 10.5812/hmj.107048
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Multisystem Inflammatory Syndrome in Children (MIS-C) Associated with COVID-19

Abstract: : The coronavirus disease 2019 (COVID-19) pandemic, with a high morbidity and mortality rate, has affected all age groups. COVID-19 infection in children usually has minimal symptoms, but the number of children with the inflammatory syndrome with clinical features similar to the Kawasaki disease has increased during the COVID-19 pandemic. Information about this emerging COVID-19 manifestation also called the multisystem inflammatory syndrome in children (MIS-C), is still incomplete. Patients typically present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…K. pneumoniae has been widely distributed in hospitals and known as an opportunistic bacterium for developing various types of nosocomial infections in hospitalized patients [19,35,36]. Antimicrobial resistance complicated the treatment of infections related to K. pneumoniae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…K. pneumoniae has been widely distributed in hospitals and known as an opportunistic bacterium for developing various types of nosocomial infections in hospitalized patients [19,35,36]. Antimicrobial resistance complicated the treatment of infections related to K. pneumoniae.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, all strains resistant to carbapenem have been evaluated every year and only two types of metallo-β-lactamases including VIM and IMP were reported, yet. Studies showed that the prevalence of VIM in Iran was lower than that of other countries such as South Korea, Japan, and France, and probably other resistance mechanisms such as efflux pumps, defects, and lack of external membrane proteins, including outer membrane protein D and carbapenem class D are involved in producing resistance to carbapenems [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…severe cardiac complications following the COVID-19 infection (9). Reports on MIS-C have shown coronary artery involvement, myocarditis, ventricular dysfunction, hemodynamic instability, and PICU admission, all of which suggest that cardiac dysfunction might be a notable risk factor for severe SARS-CoV-2 infection in pediatrics (10). Therefore, a literature review in this regard would be beneficial.…”
Section: Contextmentioning
confidence: 99%
“…Based on reports on this syndrome, persistent fever (4-6 days) and gastrointestinal symptoms (e.g., abdominal pain) are the common presentation in almost all children. 22 The following symptoms have occurred in at least half of the patients: rash, conjunctivitis, mucous membrane involvement, neurological symptoms (e.g., headache), cardiac involvement, and respiratory symptoms (e.g., tachypnea and labored breathing). Other clinical manifestations such as sore throat, myalgia, swollen hands/feet, and lymphadenopathy have also been seen in less than 20% of MIS-C patients.…”
Section: Multisystem Inflammatory Syndrome In Children Versus Kawasaki Diseasementioning
confidence: 99%